A new Calamiana species (Teleostei: Gobiidae) from brackish waters of northern Taiwan - Chen, I-Shiung; Shao, Kwang-Tsao; Huang, Shih-Pin (Zootaxa, 2024)
A new species of brackish water goby, Calamiana taiwanensis sp. nov., from northern Taiwan is described in this paper. This new species is characterized by the following unique combinations of features: (1) second dorsal fin rays I/7–8, anal fin rays I/7–8; (2) longitudinal scale rows 34–36; (3) first dorsal fin triangular, second to third spines filamentous in adult males; and (4) specific head pore system: anterior termination with a pair of head pores σ and λ, median interorbital region with a pair of pores κ1 and κ, postorbital region with a pair of pores ω, lateral termination with a pair of pores α, upper margin of preopercular region with a pair of pores β and ρ. The present study revealed that the head pore pattern is varied among the species of genus Calamiana, therefore this feature can be regarded as an important character for the species identification within Calamiana.